Uji Tarik Dan Struktur Mikro Karbon Rendah Dipanaskan Dengan Suhu 600?C Tempering Dengan Air Aki Dan Udara - Mas Intani Sigit Nurwono; Ahmadin Ahmadin; Lelawati Lelawati (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2022)
The results of the tensile test on a low carbon steel plate ST 37 with a temperature of 600°C for 30 minutes then Tempering with battery water, the average non-treated tensile strain results in the yield strain uy = 16.68 Kgf /mm2 ultimate strain ou = 27.54 Kgf /mm2 breaking strain uf = 22.57 Kgf /mm2. The average result of tensile strain in tempering with air is obtained yield strain uy = 20.42 Kgf/mm2 ultimate strain ou = 26.02 Kgf / mm2 breaking strain uf = 22.19 Kgf / mm2. Result rat.a the average dance strain in tempering using battery water obtained true strain uy = 10.92 Kg /mm2 ultimate strain ou = 19.48 Kg/mm2 breaking strain uf = 21.73 Kgf /mm2 .Worst battery water as a medium refrigerant that can reduce tensile strength compared to air cooling. The results of the photo of the microstructure of the ST 37 low carbon steel plate which were heat treated at 600oC were obtained with the microstructure results with the grain size, namely Non Treatment 12.85 µm, air 15.88 m, and Battery Water 11.53 µm. the highest is with air grain size of 15.88 µm and the lowest is water battery 11.53 µm which experienced a large decrease compared to non-treatment of 12.85 µm